Beginnings in North Sámi - Julien, Marit (2013)
In North Sámi, inceptives can be formed with the inceptive verb álgit, with the morphologically bound form -goahtit, or by changing the theme vowel of the base verb. The syntactic properties of these inceptives indicate that -goahtit is an auxiliary, and so is álgit when it takes a verbal complement. These inceptive auxiliaries are located below tense, and also below obligational and permissive modals, conditional mood, negation, and the head encoding progressive aspect,while they are located above causative, passive and frequentative aspect. The position of inceptive auxiliaries in North Sámi is not in accordance with neither of the two positions for inceptives suggested by Cinque (2006),since on Cinque’s proposal, inceptives that are below modals should also be below the causative and the passive. The North Sámi inceptives álgit and -goahtit are also problematic for Fukuda (2008), since they are located higher that any of the two inceptive positions identified by him. The inceptives involving change of theme vowels could however be associated with Fukuda’s higher inceptive position, since they take VP as their complement. Notably, álgit can also appear with only nominal dependents, and I argue that it is then the main verb of the clause.